Dynamics of nitrogenase cofactor elements and resource limitation of asymbiotic biological nitrogen-fixation during long-term pedogenesis - O. M. Butler; G. Liang; S. Matsumura; C. R. Chen; B. Kaiser; C. R. Warren (Plant and Soil, 2026)
Background and aims Biological nitrogen fixation (BNF) is central to long-term pedogenesis and overall terrestrial ecosystem development. Rates of asymbiotic BNF are potentially constrained by carbon (C), phosphorus (P), and/or nitrogenase cofactor elements (e.g., iron [Fe], vanadium [V], and molybdenum [Mo]), but our understanding of the biogeochemical trajectories of cofactor elements throughout pedogenesis is limited. Methods Using a ~ 700 ka pedogenic chronosequence at Cooloola in eastern Australia, we quantified P, Fe, V, and Mo in soil and litter and tested for C (i.e., energy), P, and/or Mo limitation of asymbiotic BNF using acetylene reduction assays. Results Cofactor elements in soil declined faster than P during pedogenesis, and their relative extractability with chelating agents increased across the chronosequence. Addition of C, P, and/or Mo did not affect asymbiotic BNF in any dune system tested. Conclusion Declines of soil P and cofactor elements during pedogenesis support an underlying influence of weathering on the biogeochemical cycling of these elements. However, dynamics of Fe, V, and Mo diverge from those of P due to increasing chelation by SOM as podzolization advances, whereas P is increasingly present in organic forms. Asymbiotic BNF is seemingly not limited by C, P, or Mo during pedogenesis at Cooloola.

Microbial phosphorus in loamy, basalt-derived forest soil is altered by plant nutritional status: a root-splitting study - O. M. Butler; C. R. Warren (Plant and Soil, 2025)
Background and aims Soil nutrient content is a major driver of primary productivity. Microbial biomass comprises a substantial soil nutrient pool, the properties of which could be shaped by plant nutrient-limitation status. We aimed to determine how plant nutrition affects soil microbial biomass nitrogen (MBN) and phosphorus (MBP), and whether such effects are linked to microbial composition. Methods To isolate the effect of plant nutrition on soil microbes, we used a split-root system with Syncarpia glomulifera Smith seedlings fertilised with either P-free Hoagland solution or a P-only solution, and quantified rhizosphere soil microbial biomass carbon (MBC), MBN, MBP, and microbial polar lipid fatty acids (PLFAs). Results Provision of N + micronutrients to S. glomulifera seedlings in basalt-derived soils led to a 19% decline in soil MBP relative to controls. This effect was not evident in comparatively P-depleted sandstone-derived soils. MBC and MBN were not affected by plant nutritional status, and neither were the abundances and composition of microbial PLFAs. Conclusion Rhizosphere microbial nutrient pools are potentially sensitive to plant nutritional status. Microbial P can be reduced when plants are P-limited. These effects are not necessarily paralleled by altered microbial composition, implicating microbial physiology as a possible driver of variation in microbial P.

Phenology and yield do not scale from single row to whole plot in chickpea and lentil - L. Lake; R. Gimenez; R. Ortega Martinez; J. L. Weller; M. Javid; J. B. Butler; L. E. James; M. F. Dreccer; R. French; C. M. Cossani; J. E. Hayes; V. O. Sadras (Euphytica, 2025)
Reliable phenotyping is critical for pre-breeding and breeding. Some traits such as herbicide tolerance are more likely to scale from plant to crop than others such as yield. Here we compared phenology, yield and its components in two arrangements—single rows and whole plots—for 10 chickpea and 10 lentil cultivars in 11 (chickpea) and 10 (lentil) Australian environments resulting from the combination of location, season, and sowing date. The cultivars were characterised for key genetic loci for phenology: Elf3a , GI and the FT gene cluster in chickpea, and GWAS-chr2 and the FTb gene cluster in lentil. Across environments, yield of chickpea ranged from 33 to 268 g per lineal m (g m −1 ) in single rows and 5 to 77 g m −1 in whole plots, and yield of lentil ranged from 20 to 174 g m −1 in single rows and 9 to 104 g m −1 in whole plots. Across environments and genotypes, time to flowering was later in 207 of 275 chickpea whole plots compared with single rows and in 175 out of 234 lentil whole plots compared with single rows. In both chickpea and lentil, flowering and podding varied with the interaction between genotype, arrangement, and environment, resulting in altered genotypic rankings between single row and whole plot within and between environments. Yield components were variably affected by the three-way interaction; biomass was the only trait showing no interaction in either crop. Broad sense heritability of seed size fell from 0.60 in whole plots to 0.37 in single rows for chickpea, and from 0.87 to 0.62 in lentil. We highlight the need to understand scaling for agronomically important traits to avoid wasteful or counterproductive phenotyping and breeding efforts.

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Animal population decline and recovery after severe fire: Relating ecological and life history traits with expert estimates of population impacts from the Australian 2019-20 megafires - Michelle Ensbey; Sarah Legge; Chris J. Jolly; Stephen T. Garnett; Rachael V. Gallagher; Mark Lintermans; Dale G. Nimmo; Libby Rumpff; Ben C. Scheele; Nick S. Whiterod; John C.Z. Woinarski; Shane T. Ahyong; et al. (Biological Conservation, 2023)

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Social dynamics of community resilience building in the face of climate change: the case of three Scottish communities - I. Fazey; E. Carmen; H. Ross; J. Rao-Williams; A. Hodgson; B. A. Searle; H. AlWaer; J. O. Kenter; K. Knox; J. R. A. Butler; K. Murray; F. M. Smith; et al. (Sustainability Science, 2021)

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

A comparison of uterine contractile responsiveness to arginine vasopressin in oviparous and viviparous lizards - Jonathan W. Paul; Joshua O. Kemsley; Trent A. Butler; Jorge M. Tolosa; Michael B. Thompson; Roger Smith; Camilla M. Whittington (Journal of Comparative Physiology B, 2020)

Advances in Mechanistic Approaches to Quantifying Biophysical Fire Effects - J. J. O’Brien; J. K. Hiers; J. M. Varner; C. M. Hoffman; M. B. Dickinson; S. T. Michaletz; E. L. Loudermilk; B. W. Butler (Current Forestry Reports, 2018)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Testing the generality of above‐ground biomass allometry across plant functional types at the continent scale - Keryn I. Paul; Stephen H. Roxburgh; Jerome Chave; Jacqueline R. England; Ayalsew Zerihun; Alison Specht; Tom Lewis; Lauren T. Bennett; Thomas G. Baker; Mark A. Adams; Dan Huxtable; Kelvin D. Montagu; et al. (Global Change Biology, 2016)
Accurate ground‐based estimation of the carbon stored in terrestrial ecosystems is critical to quantifying the global carbon budget. Allometric models provide cost‐effective methods for biomass prediction. But do such models vary with ecoregion or plant functional type? We compiled 15 054 measurements of individual tree or shrub biomass from across Australia to examine the generality of allometric models for above‐ground biomass prediction. This provided a robust case study because Australia includes ecoregions ranging from arid shrublands to tropical rainforests, and has a rich history of biomass research, particularly in planted forests. Regardless of ecoregion, for five broad categories of plant functional type (shrubs; multistemmed trees; trees of the genus Eucalyptus and closely related genera; other trees of high wood density; and other trees of low wood density), relationships between biomass and stem diameter were generic. Simple power‐law models explained 84–95% of the variation in biomass, with little improvement in model performance when other plant variables (height, bole wood density), or site characteristics (climate, age, management) were included. Predictions of stand‐based biomass from allometric models of varying levels of generalization (species‐specific, plant functional type) were validated using whole‐plot harvest data from 17 contrasting stands (range: 9–356 Mg ha −1 ). Losses in efficiency of prediction were stand ‐level biomass prediction was 99%, with a mean absolute prediction error of only 13%. Hence, for cost‐effective prediction of biomass across a wide range of stands, we recommend use of generic allometric models based on plant functional types. Development of new species‐specific models is only warranted when gains in accuracy of stand‐based predictions are relatively high (e.g. high‐value monocultures).

2nd International Conference on Progressive Multifocal Leukoencephalopathy (PML) 2015: JCV virology, progressive multifocal leukoencephalopathy pathogenesis, diagnosis and risk stratification, and new approaches to prevention and treatment - Andriani C. Patera; Scott L. Butler; Paola Cinque; David B. Clifford; Robert Elston; Robert L. Garcea; Eugene O. Major; Dejan Pavlovic; Ilse S. Peterson; Anne M. Ryan; Kenneth L. Tyler; Thomas Weber (Journal of NeuroVirology, 2015)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Skeletal muscle adaptations to physical inactivity and subsequent retraining in young men - E. L. Campbell; O. R. Seynnes; R. Bottinelli; J. S. McPhee; P. J. Atherton; D. A. Jones; G. Butler-Browne; M. V. Narici (Biogerontology, 2013)

Hyperglycemic oxoaldehyde, glyoxal, causes barrier dysfunction, cytoskeletal alterations, and inhibition of angiogenesis in vascular endothelial cells: aminoguanidine protection - Sean M. Sliman; Timothy D. Eubank; Sainath R. Kotha; M. Lakshmi Kuppusamy; Shariq I. Sherwani; Elizabeth Susan O’Connor Butler; Periannan Kuppusamy; Sashwati Roy; Clay B. Marsh; David M. Stern; Narasimham L. Parinandi (Molecular and Cellular Biochemistry, 2010)

Chelate-Assisted Phytoextraction of Lead from a Contaminated Soil Using Wheat ( Triticum aestivum L.) - M. F. T. Begonia; G. B. Begonia; A. Butler; M. Burrell; O. Ighoavodha; B. Crudup (Bulletin of Environmental Contamination and Toxicology, 2002)

Opposite changes in myosin heavy chain composition of human masseter and biceps brachii muscles during aging - M. Monemi; P.-O. Eriksson; F. Kadi; G. S. Butler-Browne; L.-E. Thornell (Journal of Muscle Research and Cell Motility, 1999)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)